Tumor detection using IRIS pattern. - Lye, Wil Liam; Ali, Chekima; Liau, Chung Fan; Jamal, Ahmad Dargham (Penerbit Universiti Sains Malaysia, 2004)
Cancer was the top 10 killer in the world. WHO reported that in years 2000, death cause by cancer patient is 6.2 million people worldwide (WHO, 2003). The earlier cancer patient know he was infected by cancer would give him higher chances to cure it. It is event better if we can predict and prevent it rather than curing it. With iridology, we could analyze cell and body activities (Lindlahr, 1919). When cells growth abnormally, iris will show some sign and changes that iridologist could tell it tumor stated to grow (Lindlahr, 1919). Thus this could prevent the tumor from grow or grow into second stage that is cancer.